Topical frankincense treatment on relieving high-risk diabetic foot in rats by reducing inflammation and improving microcirculation - Ma, Si-Yuan; Yin, Xin; Zhang, Zhao; Li, Yu-Sang; Tang, He-Bin (Frontiers in Pharmacology, 2025)
BackgroundFrankincense, an ancient aromatic substance known for promoting blood circulation, is widely used in traditional Chinese medicine to treat skin lesions.MethodsThis study aimed to evaluate the efficacy and underlying mechanisms of frankincense oil extract (FOE) in addressing high-risk diabetic foot by improving microvascular circulatory disorders. The vascular repair effects of FOE were assessed in a streptozotocin-induced high-risk diabetic foot animal model. Various evaluations were performed, including infrared thermometry, motor nerve conduction velocity (MNCV) testing, laser Doppler flowmetry (LDF), hematoxylin and eosin (H&E) staining, and immunohistochemical analyses for CD31, TRPV3, β-catenin, MMP-9, and COX-2 expressions.ResultsThe results showed that, the femoral arteries, plantar arteries, and microvessels in high-risk diabetic foot rats displayed significant damage, evidenced by reduced blood flow velocity, ruptured vascular intima, and disorganized endothelial fibers. FOE treatment restored temperature and blood flow velocity in the foot and increased MNCV. Furthermore, FOE improved blood circulation, reversed the reduced expression of CD31, enhanced nerve sensitivity by up-regulating TRPV3 expression, and exhibited anti-inflammatory effects by reducing the overexpression of β-catenin, MMP-9, and COX-2.ConclusionFOE effectively prevents high-risk diabetic foot by repairing vascular damage, restoring blood circulation, enhancing nerve sensitivity, and suppressing inflammatory cell infiltration. Therefore, these findings highlight the potential clinical value of FOE in managing diabetic complications.